Prostate cancer aggressiveness and financial toxicity among prostate cancer patients. Issue 1 (5th September 2022) - KC, Madhav; Oral, Evrim; Rung, Ariane L.; Trapido, Edward; Rozek, Laura S.; Fontham, Elizabeth T. H.; Bensen, Jeannette T.; Farnan, Laura; Steck, Susan E.; Song, Lixin; Mohler, James L.; Khan, Saira; et al.
Abstract: Introduction: Financial toxicity (FT) is a growing concern among cancer survivors that adversely affects the quality of life and survival. Individuals diagnosed with aggressive cancers are often at a greater risk of experiencing FT. The objectives of this study were to estimate FT among prostate cancer (PCa) survivors after 10−15 years of diagnosis, assess the relationship between PCa aggressiveness at diagnosis and FT, and examine whether current cancer treatment status mediates the relationship between PCa aggressiveness and FT. Methods: PCa patients enrolled in the North Carolina‐Louisiana Prostate Cancer Project (PCaP) were recontacted for long‐term follow‐up. The prevalence of FT in the PCaP cohort was estimated. FT was estimated using the COmprehensive Score for Financial Toxicity, a validated measure of FT. The direct effect of PCa aggressiveness and an indirect effect through current cancer treatment on FT was examined using causal mediation analysis. Results: More than one‐third of PCa patients reported experiencing FT. PCa aggressiveness was significantly independently associated with high FT; high aggressive PCa at diagnosis had more than twice the risk of experiencing FT than those with low or intermediate aggressive PCa (adjusted odds ratio [aOR] = 2.13, 95% CI = 1.14−3.96). The proportion of the effect of PCa aggressiveness on FT, mediated by treatment status, was 10%, however, the adjusted odds ratio did not indicate significant evidence of mediation by treatment status (aOR = 1.05, 95% CI = 0.95−1.20). Conclusions: Aggressive PCa was associated with high FT. Future studies should collect more information about the characteristics of men with high FT and identify additional risk factors of FT.